2018
DOI: 10.1159/000490422
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Imaging Predictors of Recurrent Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: Background: Predictors of recurrent ischemic stroke are less well known in patients with a recent ischemic stroke than in patients with transient ischemic attack (TIA). We identified clinical and radiological factors for predicting recurrent ischemic stroke in patients with recent ischemic stroke. Methods: A systematic search in PubMed, Embase, Cochrane Library, and CINAHL was performed with the terms “ischemic stroke,” “predictors/determinants,” and “recurrence.” Quality assessment of the articles was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 35 publications
4
45
1
Order By: Relevance
“…Although seldom referred in the literature (1,4), the male sex was also an independent predictor of readmission/death in our study; this might be due to their proneness to recurrent IS (42); nevertheless, this hypothesis is not consensual in the literature (43).…”
Section: Discussioncontrasting
confidence: 59%
“…Although seldom referred in the literature (1,4), the male sex was also an independent predictor of readmission/death in our study; this might be due to their proneness to recurrent IS (42); nevertheless, this hypothesis is not consensual in the literature (43).…”
Section: Discussioncontrasting
confidence: 59%
“…A recent study from China has shown that the incidence of recurrent stroke has increased 3-fold between 1992 and 2012 [3]. Age [4], dyslipidemia [5], smoking [6], diabetes, hypertension, homocysteine levels, atrial fibrillation [1], metabolic syndrome [7] and other risk factors [8][9][10] are associated with recurrent stroke. Indeed, a recent study has shown that hypertension, prior symptomatic stroke and chronic infarcts on MRI were independently associated with recurrent stroke and this also doubled the all-cause mortality [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we showed that recurrence risk estimation can be significantly improved by adding CT-derived predictors to a model incorporating clinical predictors. Although stroke subtype was a significant predictor of recurrent ischemic stroke in previous studies, this predictor did not have added value to the clinical prediction model in our study population [4]. The stroke etiology was determined using the TOAST classification [14].…”
Section: Discussionmentioning
confidence: 77%